Editorial - Aguiar, André Effgen; C. de A. Oliveira, Grassinete (The ESPecialist, 2023)
After four years of denialism and explicit attacks on education and science, we hope in the Freirean sense that, as an ontological necessity, we need it to, through practice, become historical concreteness. There is no hope in/through waiting, but through reflection-action, through clash and debate, through criticality, which we can hope and believe in social transformation. It is with this understanding that we wish the government that began in 2023 to hope in the movement for social change, to look and act in favor of the underserved and underserved in this country, to embrace education and science as drivers of a better country.